Young people, strategies and processes of globalization / fragmentation in the school space of the city of Tandil, Province of Buenos Aires, Argentina (Praxis Educativa, 2022)
This article presents advances in the research carried out in 2019, within the framework of the postdoctoral work plan called: Educational inequality in contexts of promotion of compulsory schooling. A study on school practices and trajectories in middle schools in the city of Tandil, Buenos Aires, Argentina. The research has as a theoretical and methodological reference the “structural-genetic” approach of Pierre Bourdieu (1987). It tries to indicate which are the relations of distinction that are established between the school reproduction strategies that secondary students deploy. To address this object of study, qualitative surveys and interviews were carried out with secondary students of the basic and oriented cycle, belonging to three Educational Institutions. There are multiple distinctions that are registered between the strategies deployed by the students of each institution. Among them - those presented here - those that refer to the use of technology and / or social networks.
Keywords: Secondary Students; Social reproduction strategies; Social networks; Globalization; Territorialization